IMPLEMENTATION OF MSMEs CREDIT PROVIDING USING THE 5C METHOD BY PT. BPR BANK BAPAS 69 ON THE KAHYANGAN TOLL TOURIST, WONOLELO VILLAGE, SAWANGAN DISTRICT, MAGELANG DISTRICT - Syarif Mutsanna, Ahmad (This journal is published by the Vocational School of Universitas Sebelas Maret., 2024)
This research aims to describe the obstacles that arise in the implementation of providing MSME credit at the Kahyangan TOL Tourism in Wonolelo Village by PT BPR BANK BAPAS 69 Magelang Regency and to describe the solutions implemented by PT BPR BANK BAPAS 69 Magelang Regency in overcoming these obstacles. It is arising from the implementation of granting MSME credit to the Wonolelo Village Kahyangan Tourism TOL. The method used is the observation method, namely observation by observing directly at the BAPAS 69 Magelang Bank Office. This research is qualitative, data collection methods using observation and interviews. The results of the observations can be stated that the implementation of providing MSME credit at the Kahyangan Toll Tour in Wonolelo village by PT BPR Bank Bapas 69 Magelang Regency, has been by the systems and procedures determined by the Main Director of PT BPR Bank Bapas 69 Magelang Regency. Systems and procedures have been implemented as they should. The systems and methods implemented do not rule out the possibility of future risks regarding the credit disbursed. To minimize credit risk, PT BPR Bank Bapas 69 Magelang Regency has implemented prudential principles through the 5 C.